Absenteeism in physical education lessons among high school students - Jastrzębska, Joanna (Contemporary problems of physical and health culture, 2022)
The aim of the study was an attempt to diagnose the phenomenon of absenteeism in PE lessons of high school youth. The method of diagnostic survey was used, 51 randomly selected students aged 14‒18 years old high school in Lodz were included in the survey. The results of the research were subjected to statistical analysis. The research results indicate that girls less often and less willingly participate in PE lessons than boys. They argue that these lessons are conducted in a boring and uninteresting manner. They are also less aware than boys that physical activity is beneficial for health and proper development of the body.